1996
DOI: 10.1111/j.1467-8624.1996.tb01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Change in Early Childhood Aggressive-Disruptive Behavior: Gender Differences in Predictions from Early Coercive and Affectionate Mother-Child Interactions

Abstract: The present study focused on mother-child interaction predictors of initial levels and change in child aggressive and disruptive behavior at school from kindergarten to third grade. Aggression-disruption was measured via annual reports from teachers and peers. Ordinary least-squares regression was used to identify 8 separate child aggression trajectories, 4 for each gender: high initial levels with increases in aggression, high initial levels with decrease in aggression, low initial levels with increases in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 44 publications
(41 reference statements)
2
92
2
1
Order By: Relevance
“…However, when data from boys and girls are analyzed separately, there can be different conclusions for boys and girls (e.g., Coie, Terry, Lenox, et al, 1995). Moreover, when sex has been explicitly tested as a moderator (i.e., Predictor × Sex Interaction), differences in specific parenting (e.g., McFaydenKetchum, Bates, Dodge, & Pettit, 1996) and peer relationship (e.g., Kupersmidt, Burchinal, & Patterson, 1995;Laird et al, 1999) processes predicting antisocial behavior development have been identified. It is not clear, however, whether sex differences are so pervasive as to indicate the need for different models for boys and girls.…”
Section: Unified Modelmentioning
confidence: 99%
“…However, when data from boys and girls are analyzed separately, there can be different conclusions for boys and girls (e.g., Coie, Terry, Lenox, et al, 1995). Moreover, when sex has been explicitly tested as a moderator (i.e., Predictor × Sex Interaction), differences in specific parenting (e.g., McFaydenKetchum, Bates, Dodge, & Pettit, 1996) and peer relationship (e.g., Kupersmidt, Burchinal, & Patterson, 1995;Laird et al, 1999) processes predicting antisocial behavior development have been identified. It is not clear, however, whether sex differences are so pervasive as to indicate the need for different models for boys and girls.…”
Section: Unified Modelmentioning
confidence: 99%
“…La escasez de trabajos que han explorado el patrón específico de inconsistencia en problemas exteriorizados e interiorizados no nos permite hacer comparaciones. Sin embargo, la relevancia de la inconsistencia en el control parental es coherente con aquellos estudios, que establecen una clara relación entre los problemas exteriorizados y la presencia de hábitos de crianza inadecuados relacionados con el control y la gestión de límites: control autoritario, control laxo y permisivo, ausencia de límites o ausencia de supervisión (McFadyen-Ketchum, Bates, Dodge y Pettit, 1996;Pettit y Dodge, 1993). En términos de inconsistencia globalmente considerada, algunos trabajos más recientes, están en sintonía con este patrón diferencial de inconsistencia interparental asociado a las manifestaciones exteriorizadas e interiorizadas.…”
Section: Discussionunclassified
“…Evidence shows that mothers' parenting style (indirect influence) influences children's aggression. For example, children of mothers who are warm, responsive and use low levels of coercion tend to be more socially competent and less aggressive with peers (McFadyen-Ketchum, Bates, Dodge, & Pettit, 1996;Mize & Pettit, 1997). The use of corporal punishments increased childhood aggressive behavior (Gershoff, 2002).…”
Section: Mothers' Reactions and Children's Aggressionmentioning
confidence: 99%